2022-LBA-790-ESGO Sentinel lymph node detection with Magtrace® in cervical cancer. (27th October 2022) - Jedryka, Marcin; Czekanski, Andrzej; Lepka, Piotr; Poprawski, Tymoteusz; Kryszpin, Marcin
Abstract : Introduction: This prospective observational study, named POEMCerca (Po lish E valuation of Magtrace® in Cer vical Ca ncer) aims to evaluate efficacy of the Magtrace® system in SLN (Sentinel Lymph Nodes) detection in early stage cervical cancer patients in comparison with the standard of care. The nanoparticle paramagnetic detection systems of SLN have been prooved so far to be comparable and non-inferior to the standard procedure of systematic lymphadenectomy in breast cancer and vulvar cancer patients. Methods: 16 patients with stage I cervical cancer received a cervical injection of superparamagnetic iron oxide tracer (Magtrace®). Magtrace® localized and detected SLN with magnetic counts and with visual inspection for their brownish colour. For each SLN the anatomic site, magnetic counts and colour was documented before biopsy. Afterwards, systematic lymphadenectomy – pelvic (PLND) and paraaortic (PALND) – in some cases (high grade tumour and/or adenocarcinoma) was performed as the standard of care. Results: SLN were detected in every patient. Bilateral SLN were found in 87.5% of cases. The mean SLN count per patient was 3.9. All SLN were assessed as brownish stained. In one SLN micrometastasis was detected. Statistic results have been presented in the table 1 . Conclusions: This preliminary study showed efficient Magtrace® detection of SLN in early stage cervical cancer patients which is not inferior to the standard of care.